A Cross-Sectional Study on the Association of Patterns and Physical Risk Factors with Musculoskeletal Disorders among Academicians in Saudi Arabia. (17th August 2020) - Algarni, Fahad Saad; Kachanathu, Shaji John; AlAbdulwahab, Sami S.
Abstract : Background . Musculoskeletal disorders (MSDs) are considered one of the most common health issues in working population and have a high social and economic impact. This study is aimed at determining the MSD patterns and associated risk factors among higher education academicians in Saudi Arabia. Methods . A cross-sectional study was conducted among higher education academicians, randomly selected from different universities within Saudi Arabia. A sample of 207 academicians participated in the present study from different faculties such as nursing, applied medical sciences, pharmacy, dentistry, computer science, science, and engineering for a period of 1 year. The Nordic Musculoskeletal Questionnaire (NMQ-E) was used to assess the MSD patterns and prevalence for the different parts of the body regions, and the Dutch Musculoskeletal Questionnaire (DMQ) was used to determine the physical risk factors associated with the working conditions in the higher academic occupations. Descriptive statistics and the Pearson chi-squared test were used for data analysis. Results . The overall prevalence rate was 42.5%, and the pattern of body parts involved was almost similar on both study variables, i.e., descending from the lower back (31.9%), followed by the neck (26.1%), knees (21.3%), shoulder (16.9%), upper back (13%), ankle and foot (10.1%), wrist and hand (7.2%), and elbow (6.3%), and the least common observed region was the hip and thigh (2.4%). The physical risk factors and its association with the body regions based on DMQ related to workload, period of use, and repetitive movements were observed in the wrist and hand (43%), followed by the neck (42%) and trunk (21%). Conclusion . The study demonstrated that the MSDs are lower among the higher academic occupations. However, the most common MSDs observed in this group of subjects are the back, neck, and knee pain, and it is found that some of the lifetime physical activities also have a significant association with these involved body regions.